Pricing of Power Derivatives - Foukal, Viktor; Witzany, Jiří, 1966-; Vacek, Vladislav; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The main target of this thesis is to summarize and demonstrate the main characteristic of power markets and trying to find out electricity spot model. Thesis starts with definition of market subjects, typology of traded contracts and description of market development with focus on South Easter Europe. Thesis continues with development of consumption function and theoretical concepts of Demand/Capacity ratio which is used in short term/spot modeling and serve to identify a risk of potential increase in volatility. After deriving fundamental models I will continue with stochastic model - Volatility Regime model with Jump diffusion. I used all these knowledge and observed patterns in order to evaluate illiquid power options with daily settlement.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses